2019
DOI: 10.1080/13880209.2019.1656257
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibitory effects of kaempferitrin on human liver cytochrome P450 enzymes

Abstract: Context: Kaempferitrinis (KF) is a bioactive flavonoid and possesses numerous pharmacological activities. However, whether KF affects the activity of human liver cytochrome P450 (CYP) enzymes remains unclear. Objective: This study investigates the effects of KF on eight major CYP isoforms in human liver microsomes (HLMs). Materials and methods: In vitro, HLMs were used to investigate the inhibitory effects of KF (100 lM) on the eight human liver CYP isoforms (i.e., 1A2, 3A4, 2A6, 2E1, 2D6, 2C9, 2C19, and 2C8),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It also showed potential effects in downregulating the immune system in mice [17]. A study by Zhang [66]. The glycosyloxyflavone apiin was measured at a high concentration (5 µg/L) in a water sample from the Bode catchment but was also obtained in two water samples from ELP at an average concentration of 2.9 µg/L.…”
Section: Distribution Of the Identified Metabolites In River Watersmentioning
confidence: 99%
“…It also showed potential effects in downregulating the immune system in mice [17]. A study by Zhang [66]. The glycosyloxyflavone apiin was measured at a high concentration (5 µg/L) in a water sample from the Bode catchment but was also obtained in two water samples from ELP at an average concentration of 2.9 µg/L.…”
Section: Distribution Of the Identified Metabolites In River Watersmentioning
confidence: 99%
“…It also showed potential effects in downregulating the immune system in mice (Guan et al 2014). A study by Zhang et al showed that kaempferitrin competitively inhibited human liver microsomal Cytochrome P450 1A2 activity at an IC 50 of 11 mg/L in vitro (Zhang et al 2019).…”
Section: Distribution Of the Identi Ed Metabolites In River Watersmentioning
confidence: 99%
“…Nicoti orin was found to protect against memory dysfunction and oxidative stress in multi-infarct dementia model rats (Huang et al 2007;Harborne and Baxter 1999). A study by Zhang et al showed that kaempferitrin competitively inhibited human liver microsomal Cytochrome P450 1A2 activity (Zhang et al 2019).…”
Section: Flavonoidsmentioning
confidence: 99%